The Effect of Human Resources, Internal Control Systems, and Information Technology on Local Government Financial Statement Consolidation - Saprudin; Febian Junaid; Mohamad Abdul Radjak Masjhur; Julie Abdullah; Nikma Bilondatu (Institut Bisnis dan Informatika Kesatuan, 2026)
This study is based on the importance of accurate, transparent, and timely consolidated financial reporting in local governments in accordance with public sector accounting regulations in Indonesia, which still face challenges related to human resource competence, internal control systems, and information technology utilization. The objective of this research is to analyze the influence of human resources, internal control systems, and information technology on local government financial statement consolidation, both partially and simultaneously. A quantitative explanatory design was employed using questionnaire data collected from financial management officials, which were analyzed using multiple linear regression. The findings indicate that all three variables have a positive and significant effect on financial statement consolidation, with the internal control system emerging as the most dominant factor, while simultaneously the three variables also show a significant joint influence on the dependent variable. The study concludes that the effectiveness of financial consolidation strongly depends on the integration of competent human resources, strong internal control mechanisms, and effective information technology utilization. The implication of this study is that local governments need to enhance human resource competencies, strengthen internal control systems, and optimize information technology usage to improve the quality of consolidated financial reporting.